Three-dimensional assessment of the judo throwing techniques frequently used in competition - Santos, L.; Fernández-Rio, J.; Ruiz, M. L.; Valle, M. D.; Callan, M.; Challis, B.; Sterkowicz, S. (Archives of Budo, 2014)
Background and Study Aim: Although the judo throwing techniques are not considered as injurious to the attacker, repetition of these techniques might cause repetitive strain type injuries. The goal of the study was knowledge about the degrees of flexion and extension and abduction and adduction of the main locomotive joints, performing the most employed throwing techniques in high-level competition. Material and Methods: Two world-class judoists, under the supervision of an elite Japanese expert, performed seoi-nage, uchi-mata, osoto-gari, ouchi-gari and kouchi-gari. They were analysed using three-dimensional technology. Results: Data of performance throws obtained from expert 1 and 2 respectively were very similar. Results indicate that systematic repetition of seoi-nage, uchi-mata and o-soto-gari can produce shoulder tendon pathologies. Long-term seoi-nage and uchi-mata practice might generate epicondylitis. Judokas who have suffered anterior cruciate ligament injuries must be careful when executing techniques that demand explosive knee extension (i.e. seoi-nage) against a great resistance. Judokas are not exposed to overuse injuries when they perform ouchi-gari and kouchi-gari throws. Conclusions: Systematic practice of the most employed judo throwing techniques in high-level judo can cause injuries by overuse in the upper-body joints (shoulder, elbow). Nevertheless, the lower-body joints (knee, ankle) do not seem to be at risk of injury by overuse.